التعليم ما قبل المدرسي ودوره في التحسيس البيئي لدى الأطفال - ابوسنينةد.عبدالله البشير; عوند. الزروق سالم (Aljameai, 2022)
الملخص: هدفت هذه الدراسة إلى التعرف عن الوسائل التي يتم استخدامها في التحسيس البيئي داخل الصف، والنشاطات اللاصفية التي تشعر أهمية البيئة لدى الأطفال، والفروق ذات الدلالة الإحصائية وفقا لمتغيرات الدراسة( النوع- المستوى التعليمي- الخبرة) ولغرض تحقيق أهداف الدراسة قام الباحثان باستخدام المنهج الوصفي التحليلي باعتباره المنهج المناسب لمثل هذه الدراسة، حيث تكون مجتمع الدراسة من جميع رياض الأطفال والبالغ عددها (15) روضة وعدد (70) معلما ومعلمة بمدينة الرياينة خلال العام الدراسي 2021/ 2022م، واعتمدت الاستبانة كوسيلة في جمع البيانات بعد التأكد من صدقها وثباتها، وتم تحليل البيانات باستخدام المنظومة الإحصائية للعلوم الاجتماعية (SPSS) من خلال المتوسطات الحسابية والانحرافات المعيارية واختبار(T.TEST)، وتوصلت الدراسة إلى أهم النتائج الآتية: أن الوسائل الأكثر استخداما في التحسيس البيئي للأطفال داخل الفصل يتم من خلال العناصر المحيطة بهم، واستخدام طريقة الرسم على الورق الكرتوني أن أكثر الوسائل استخداما في التحسيس البيئي لدى الأطفال اللاصفية وتشعرهم بأهمية البيئية القيام بالرحلات الترفيهية. Abstract: This study aims to identify the means that are used for triggering environmental awareness in classroom children, extracurricular activities that arouse the children’s attention to the importance of the environment. This study also aims to investigate the statistical significant differences according to the study variables (gender - age - educational level - experience). In order for the study to achieve its objectives, the researchers used the descriptive analytical approach as the main method in this study. The subjects of the study were children from (15) kindergartens and (70) teachers from those kindergarten’s in the city of Rayyana. The study was conducted during the school year 2021/2022. For data collection, a questionnaire was adopted as a means after ensuring its validity and reliability. The data was analyzed using the Statistical System for Social Sciences (SPSS) through arithmetic averages and standard deviations and (T.TEST) test The findings of the study are summarized in the followin: The most widely used means of arousing children’s environmental awareness in classroom is utilising surrounding elements and/or drawing on cardboards,The most extra-curricular means that is widely used for arousing children’s environmental awareness among children is taking recreational trips.